Evolution and Simulation Analysis of Digital Transformation in Rural Elderly Care Services from a Multi-Agent Perspective in China - Zheng Wen; Ming Mo; Jin Xu (Mathematics)
Amid accelerating population aging and the rapid evolution of digital technologies, the digital transformation of rural elderly care services has become a pivotal strategy for restructuring the rural elderly care system. This study identified the local government, rural elderly care service centers, and the elderly population as the principal stakeholders, and developed a tripartite evolutionary game-theory model to examine the dynamic strategic interactions among these actors under the influence of digital technologies. The model further investigated the evolutionary trajectories and equilibrium conditions of their behavioral strategies. Numerical simulations conducted via MATLAB were employed to validate and visualize the model outcomes. The findings revealed the following. (1) The evolutionary equilibrium of digital elderly care service development in rural areas is jointly determined by the strategic choices of the three parties, with its stability shaped by a complex interplay of cost structures, incentive mechanisms, and utility outcomes. (2) Cost factors exhibit heterogeneous effects across stakeholders. Specifically, excessive regulatory costs diminish the performance incentives of local governments, digital infrastructure and operational expenditures influence service centers’ capacity for precision-oriented service delivery, and the participation of the elderly is constrained by affordability thresholds. (3) Local government behavior demonstrates a pronounced sensitivity to incentives. In particular, rewards and social reputation conferred by higher-level governmental bodies exert a significantly stronger influence than punitive measures. (4) Government subsidies for digital transformation enhance cross-stakeholder synergy through dual transmission channels. Nonetheless, excessive subsidies may escalate fiscal risk, while moderately calibrated penalty mechanisms effectively curb moral hazard within service centers. This study advances theoretical understanding of multi-stakeholder coordination in the context of digitally enabled rural elderly care and provides actionable insights for policymakers aiming to formulate interest-aligned strategies and construct resilient, intelligent governance systems for elderly care.